High‐performance work systems and work–family interface: job autonomy and self‐efficacy as mediators. (9th July 2019) - Wattoo, Mashal Ahmed; Zhao, Shuming; Xi, Meng
Abstract : The purpose of this study is to examine the relationship between high‐performance work systems (HPWS) and the work–family interface (i.e. work–family conflict (WFC) and work–family facilitation (WFF)) in a Chinese context. We used job autonomy and self‐efficacy as an underlying mechanism for describing the relationship between HPWS and the work–family interface. Using data from 152 HR managers and 1324 employees, we found that the HPWS was positively associated with both job autonomy and self‐efficacy. We observed that self‐efficacy was an important mechanism to explain the relationship between HPWS and WFF and WFC. We also observed that job autonomy mediated the relationship between HPWS and WFF, but its presence was not significant between HPWS and WFC. One unique contribution of the study is that the authors extended the job demands–resources model to Chinese employees, confirming that self‐efficacy is an important mechanism linking HPWS with WFC and WFF. Practical implications and future research directions are discussed. Key points: Implementation of high‐performance work practices is important to improve work–family facilitation and reduce work–family conflict. Self‐efficacy is an important mechanism to reduce work–family conflict. Data were collected from 152 HR managers and 1324 Chinese employees.